Introduction to Cast Removable Partial Dentures and Surveying - Cecilia Dong (Association of American Medical Colleges, 2010)
Abstract Clear visualization of dental materials and technical procedures demonstrated in real time through videos adds another dimension to student learning that is not available from written/verbal descriptions or still images/teaching aids alone. This module includes a series of 11 short video clips that provide an introduction to the parts of a cast removable partial denture (RPD) and the steps involved in the surveying process. Surveying is an essential skill that dental students need to develop to evaluate and design cast RPDs. Verbal descriptions of surveying in lectures and written descriptions in RPD text books and laboratory manuals are insufficient to prepare second-year dental students learning how to survey a partially edentulous cast for the first time. These videos were produced to fill this gap and have received positive feedback from students and course instructors over the past three years. When students have viewed the videos before the first lab and can follow the videos while completing their first surveying exercise in the lab, they are able to quickly master the criteria used to measure competency in surveying. The videos can also be used to review concepts for students currently in the course and courses for the more advanced dental student.